Based on the zero product property, if the product of two factors equals zero, then at least one of the factors must be equal to zero.
For the equation \((2x - 3)(x + 2) = 0\), this means that either:
- \(2x - 3 = 0\) or
- \(x + 2 = 0\)
Solving these equations:
-
For \(2x - 3 = 0\): \[ 2x = 3 \implies x = \frac{3}{2} \]
-
For \(x + 2 = 0\): \[ x = -2 \]
Thus, the statements that must be true about this equation are that either \(x = \frac{3}{2}\) or \(x = -2\). In summary, the solutions to the equation \((2x - 3)(x + 2) = 0\) are \(x = \frac{3}{2}\) and \(x = -2\).